Effect Of Budget Participation, Budget Goals and The Role Of Financial Management Management Regional To Local Government Performance (Case Study On Mamuju Regency Government) - Hasbi, Aulia Reski; Mas'ud, Masdar; Junaid, Asriani (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
This study aims to determine and describe the effect of budget participation and budget targets as well as the role of regional financial management management on the performance of the local government of Mamuju Regency. This research uses quantitative research methods with a survey research form. The population of this study was 32 SKPD questionnaires distributed to each of 3 leaders representing Management, and 1 employee staff (treasurer) in order to get 128 samples. The sampling method uses Purposive Sampling techniques, respondents in this study data testers are carried out using descriptive statistics, data quality tests, classical assumption tests, and hypothesis testing. The results of this study show that the variable of participation in the budget has a positive but not significant effect on the performance of local governments, while the variables of clarity of budget targets and the managerial role of financial managers have a positive and significant effect on the performance of the local government of Mamuju district.